Studi Kasus : Pengalaman Peningkatan Harga Diri Orang dengan HIV AIDS di Kota Semarang - Chalimatus Sa’diyyah; Laura Khattrine Noviyanti; Nanang Khosim Azhari (Jurnal Anestesi, 2024)
HIV is a virus that weakens the human immunity system while AIDS is a condition of an individual infected by the virus. The factors of HIV-AIDS transmission include sexual intercourse. Self-dignity is the most important component of humans. Self-dignity has an important role to improve and keep individuals' expectations about health. This research sought and described the experience of improved self-dignity in HIV-AIDS patients. This qualitative research applied a study case approach. The participants consisted of 6 persons. The researchers collected the data with interviews, observation, and field notes. The researchers transcribed the interview results verbally and manually. Then, the researchers analyzed the data until finding categories. The applied analysis was Miles & Huberman. The research lasted for two months and found five categories. They were: 1) the cause of HIV/AIDS on the participants 2) the effects of initial HIV/AIDS diagnosis on the patients 3) the method of the patients to improve self-dignity 4) the internal and external supports as the motivation to live on 5) the method of the patients to keep healthy.